2017
DOI: 10.1186/s40001-017-0288-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the genome-wide association study of chronic hepatitis B susceptibility in Asian population

Abstract: Chronic hepatitis B (CHB) is the most common chronic liver disease resulting from viral infection and has become a serious threat to human health. Each year, about 1.2 million people in the world die from diseases caused by chronic infection of hepatitis B virus. The genetic polymorphism is significantly associated with the susceptibility to chronic hepatitis B. Genome-wide association study was recently developed and has become an important tool to detect susceptibility genes of CHB. To date, a number of CHB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Interestingly, the IL1B rs16944 allele C has been identified as a genetic marker for the development of hepatocarcinoma in patients with chronic HBV infection [ 31 ]. Furthermore, genome-wide association study in southwest China revealed 6 new loci, including the rs16944 SNP in the IL1B gene, associated with an increased prevalence rate of chronic hepatitis B [ 32 ]. Altogether, the rs16944 may be a genetic modifier of hepatitis caused by either HBV or HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the IL1B rs16944 allele C has been identified as a genetic marker for the development of hepatocarcinoma in patients with chronic HBV infection [ 31 ]. Furthermore, genome-wide association study in southwest China revealed 6 new loci, including the rs16944 SNP in the IL1B gene, associated with an increased prevalence rate of chronic hepatitis B [ 32 ]. Altogether, the rs16944 may be a genetic modifier of hepatitis caused by either HBV or HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified single nucleotide polymorphisms (SNPs) in human leukocyte antigens (HLA) that have been associated with the outcome of HBV infection, either with clearance or progression of chronic infection, although some findings were not subsequently supported in other manuscripts. Among the more in depth characterized, it has been found that HLA-DP (rs3077 and rs9277535) and HLA-DQ (rs7453920 and rs2856718) SNPs were associated to HBV persistence[ 25 - 27 ] Notably, different studies have also identified several HLA polymorphisms associated with the response to the HBV vaccine[ 28 , 29 ]. Additionally, it was also reported that cytokine, chemokine, toll like receptor, sodium taurocholate cotransporting polypeptide, and vitamin D-related genes may influence the clinical outcomes of HBV infection[ 24 , 30 , 31 ].…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…16 A number of CHB-related susceptibility loci and genetic regions have been reported, among which 26 important candidate single-nucleotide polymorphisms (SNPs) were identified. 17 Therefore, the variations caused by SNPs that affect expression of cytokines that regulate and initiate the immune system such as IL-12B may reduce the ability of the immune system to elicit a response against viral infections. 18 The active cytokine is a 70 kDa heterodimer comprising two covalently linked proteins of 35 kDa (p35) and 40 kDa (p40) 19 ; each subunit is encoded on different chromosomes.…”
Section: Introductionmentioning
confidence: 99%